State of disrepair : fixing the culture and practices of the State Department - Schake, Kori N. (Hoover Institution Press publication ;, 2012)
Kori Schake shows how the deficiencies in focus, education, and programmatic proficiency impede the work of the State Department and suggests how investing in those areas could make the agency significantly more successful at building stable and prosperous democratic governments around the world. She explains why, instead of burdening the US military with yet another inherently civilian function, work should focus on bringing those agencies of the government whose job it is to provide development assistance up to the standard of success that our military has achieved. Schake presents a vision of what a successful State Department should look like and seeks to build support for creating it, a State Department that makes possible the projection of US civilian power as well as US military force.